Case studies of the most popular European destinations for mobile students from Russia, Eastern Europe, Caucasus, and Central Asia - Chankseliani, M; Hessel, G (Centre for Comparative and International Education, University of Oxford, 2016)
Studying in Europe has become increasingly popular among students in Russia, Eastern Europe, Caucasus, and Central Asia since the second half of the 1990s. Student flows from former Soviet countries to Europe have never been as abundant as they are today. This trend is due to the surge in university enrolments in general, a growth in opportunities to study abroad as a consequence of the economic development of former Soviet countries, and the rapid internationalisation of higher education systems in Europe. Repressive measures that the Union of Soviet Socialist Republics (USSR) had in place during the Cold War did not allow its citizens to travel internationally and kept international migration well below the levels that may have occurred otherwise. While the USSR sent very few students abroad, its dissolution disrupted the period of isolation from world markets, with the citizens of former Soviet countries facing fewer constrains on travel and migration (Chankseliani, 2015). The heterogeneous pathways of development of these countries led to dissimilar educational and labour market opportunities for young people, as well as distinct patterns of student mobility.